Effect of the Site of Fixation of Foley Catheter in the Cervix on the Collected Embryos in the Cow: Wafir Mahdi SALEH and Ihsan H. AL-TIMIMI - SALEH, Wafir Mahdi (The Iraqi Journal of Veterinary Medicine, 2012)
Thirty six trials of flushing with riched Delbeco`s phosphate buffer media applied in this study using a plastic two ways folly catheter, introduced by metal robe inside the cervix of donor cows and by air bubble fixed it in the cervical canal in 3 positions, one near the cervico-vaginal opening or at the first third of the cervical canal, the 2nd one at the middle third of the cervical canal and the 3rd one near the utero-cervical opening or at the last third of the cervical canal. The process of flushing was carried out after the fixation of the folly catheter in the three sites and the number of embryos collected by each collection site.The results showed that the number of embryos detected in the third method where the fixation was in the last 3rd of cervix relatively more than the other two sites.The study showed that the position and the fixation of the folly catheter in the last 3rd of the cervical canal and toward the utero-cervical opening gave more number of embryos than the two other sites upon the process of flushing and collection of embryos.